2001
DOI: 10.1126/science.1060939
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Anions as the Voltage Sensor of Prestin, the Outer Hair Cell Motor Protein

Abstract: Outer hair cells (OHCs) of the mammalian cochlea actively change their cell length in response to changes in membrane potential. This electromotility, thought to be the basis of cochlear amplification, is mediated by a voltage-sensitive motor molecule recently identified as the membrane protein prestin. Here, we show that voltage sensitivity is conferred to prestin by the intracellular anions chloride and bicarbonate. Removal of these anions abolished fast voltage-dependent motility, as well as the characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
511
13
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(564 citation statements)
references
References 26 publications
38
511
13
2
Order By: Relevance
“…Two membrane proteins, i.e., a fructose transporter, GLUT-5 (Géléoc et al 1999), and an anion/ sulfate transporter, prestin (Zheng et al 2000), were proposed to be this motor. Although recent studies have ascertained that the motor protein is prestin, not GLUT-5 (Belyantseva et al 2000;Oliver et al 2001;Liberman et al 2002), constituents of the 10-nm particles observed in the OHC lateral membrane have remained unclear; in other words, it is unknown whether these 10-nm particles are indeed exclusively constituted of prestin molecules or rather a complex of GLUT-5 and prestin molecules. In the present study, we found particle-like structures with a diameter of 8-12 nm in the prestin-transfected CHO plasma membrane.…”
Section: Imaging Of Membrane Protein Prestinmentioning
confidence: 99%
See 1 more Smart Citation
“…Two membrane proteins, i.e., a fructose transporter, GLUT-5 (Géléoc et al 1999), and an anion/ sulfate transporter, prestin (Zheng et al 2000), were proposed to be this motor. Although recent studies have ascertained that the motor protein is prestin, not GLUT-5 (Belyantseva et al 2000;Oliver et al 2001;Liberman et al 2002), constituents of the 10-nm particles observed in the OHC lateral membrane have remained unclear; in other words, it is unknown whether these 10-nm particles are indeed exclusively constituted of prestin molecules or rather a complex of GLUT-5 and prestin molecules. In the present study, we found particle-like structures with a diameter of 8-12 nm in the prestin-transfected CHO plasma membrane.…”
Section: Imaging Of Membrane Protein Prestinmentioning
confidence: 99%
“…In an early study, this motor protein was proposed to be GLUT-5 (Géléoc et al 1999). Although GLUT-5 has been ruled out as being this motor protein (Belyantseva et al 2000;Oliver et al 2001;Liberman et al 2002), it is unclear whether prestin and GLUT-5 form a complex in the plasma membrane. Therefore, it still remains unknown whether the 10-nm particles seen in EM/AFM images are only prestin or rather a complex of GLUT-5 and prestin molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral region lacks voltage-gated channels but holds thousands of integral membrane proteins ( 7000/lm 2 ) (Gulley and Reese 1977;Forge 1991;Kalinec et al 1992;Huang and Santos±Sacchi 1993;Kalinec and Kachar 1995;Souter et al 1995;Holley 1996;Santos±Sacchi et al 1997). These integral membrane proteins are currently associated with the motor molecules responsible for the reversible and very fast changes in cell length known as OHC electromotility (Geleoc et al 1999;Zheng et al 2000;Belyantseva et al 2000;Oliver et al 2001). The basal region, in contrast, displays a signi®cant number of voltage-gated channels but has few motor molecules Santos±Sacchi et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfate reduces somatic electromotility [6] acting directly on prestin [10]. Replacement of intracellular chloride with sulfate, in our experiment, did not appear to influence the efficacy of the extracellular applied 9AC.…”
Section: Discussionmentioning
confidence: 61%